Penal Policy on Assets Recovery on Corruption Cases in Indonesia - Wahyudi, Sugeng (JILS (Journal of Indonesian Legal Studies), 2019)
Corruption is an extraordinary crime whose impact on actions can undermine a country, corruption is increasingly becoming increasingly common. Even though not a few of the former state officials or state officials until all the villages have felt how fierce the law enforcers, especially the KPK arrested them all, either hand-grabbing operations or the development of public reporting, impressed by them all were endless corruptors kept appearing , Law enforcement in this modern era is not only concerned with prosecution and prevention, in this case corruption is regulated by the return of state losses as asset recovery, which in turn will maximize the return of state losses from corruptors. As for the problems of this study are: 1. Why is the politics of criminal law (strafrechtpolitiek) in the framework of restoring state losses not significant with the real state losses due to criminal acts of corruption? 2. How is the politics of criminal law ideally (strafrechtpolitiek) implemented so that the maximum return on state losses due to corruption? The benefits of research consist of theoretical benefits and practical benefits. Theoretical benefits are expected to contribute to theoretical thinking in criminal law, especially concerning the politics of criminal law in the context of eradicating criminal acts of corruption. Practical benefits are expected to be able to provide information scientifically to the public both in general and specifically. This study uses a descriptive legal approach that is supported by primary, secondary and tertiary data obtained from documentation and literature studies then analyzed using qualitative descriptive analysis methods. The results showed that the Politics of Criminal Law in the Framework of Returning State Losses due to Corruption in Indonesia was not maximal, as evidenced by the lack of maximum or no maximum return on state losses for corruption, therefore recommendations on simplifying regulations in terms of early prevention or since In the beginning of corruption cases which caused a lot of damage to the state's financial need, there was a special formulation so that the handling could be maximized to restore state losses in corruption.